PEMANFAATAN BUKU TEKS DALAM MENUNJANG PEMBELAJARAN MATEMATIKA DI SEKOLAH MENENGAH KEJURUAN NEGERI I KEBUMEN TAHUN 2019 (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2021)
The research was conducted with the aim to obtain the information about: (1) the meaning of a text book for the teachers in mathematics learning at SMK Negeri 1 Kebumen. (2) The criteria of selecting a text book for the teachers in mathematics learning at SMK Negeri 1 Kebumen. (3) The use of a text book for the teachers in mathematics learning process at SMK Negeri 1 Kebumen; and (4) the obstacles which are faced by the teachers in using a text book in mathematics learning. This research is descriptive qualitative research. The research was done at SMK Negeri 1 Kebumen. The data collection used in this research are observation, interview, and documentation. The data sources of the research are informants (mathematics teachers), documents (text book), the setting and the event (class and learning process). The data analysis used is interactive analysis which consists of three phases: data reduction, data performance, and giving conclusion. The research shows that the text book has essential meaning for the teachers. (1) The text book can be functioned as the learning source and learning media of mathematics. The text book contents of materials, illustrations, and kinds of evaluation, therefore, the goal of mathematics learning can be achieved optimally. (2) The first criteria of selecting text bookis based on the relevancy of the material included and the curriculum standard. The further criteria can be seen from the completeness of the material, the number of illustrations, and kinds of exercises and evaluation. (3) In mathematics learning, there are two utilizations of text book: the use of text book for the students who have owned the book and the use of text book for the students who have not owned the book. If the students do not have the book, the students can borrow the book from the library. (4) The obstacles in using the text book are the price which is relatively expensive, the limitation of the text book, the role of library has not been optimum, and the limitation of the use of information technology from the internet. Those obstacles can be barrier factors in utilizing the text book maximally.
Keywords: text book; mathematics learning; utilizing